A controlled trial on the effect of feeding dietary chestnut extract and glycerol monolaurate on liver function in newborn calves. Issue 1 (10th March 2014) - Wieland, M.; Weber, B. K.; Hafner‐Marx, A.; Sauter‐Louis, C.; Bauer, J.; Knubben‐Schweizer, G.; Metzner, M.
Summary: Beginning in the fall of 2010, an increasing and alarming number of cases of calves suffering from liver dystrophy were reported in the south of Germany. An epidemiological investigation was carried out by the authors between November 2010 and July 2011, leading to the implication of a commercial dietary supplement as the potential cause for this outbreak. The components of this product were first tested in a cell culture model and two of them (dietary chestnut extract and glycerol monolaurate) showed a cytotoxic effect. The objective of this study was therefore to evaluate the effect of supplemental feeding of both components alone or in combination on liver function in newborn calves on a commercial dairy farm. Ten calves were enrolled in each of the three treatment groups and the control group (group O) following a blocked design. Treatment consisted of supplementation with chestnut extract at 0.02% of birth body mass (BM) (group C), supplementation with glycerol monolaurate at 0.006% of BM (group G) or a combined treatment (group CG) for five consecutive days. The effect of treatments on liver function was evaluated clinically and by measurement of glutamate dehydrogenase (GLDH) and aspartate aminotransferase (AST) activities as well as the determination of the concentrations of glucose, L‐lactate and total bilirubin in serum. There was a significant increase in GLDH and AST activities and a significant decrease in glucose concentration in treatment groups C and CG compared with the control group (p ≤ 0.035), whereas no difference was shown for group G. Survival was significantly decreased in groups C (p = 0.029) and CG (p = 0.001) compared with both group G and the control group. These results suggest that dietary chestnut extract in an amount of 0.02% of BM alone or in combination has a toxic effect on liver function in newborn calves.